Employee Performance Model Based on Green OCB and Green Transformational Leadership Through Green Work Engagement - Iim Yulianti; Indah Lestari; Ahmad Ahmad (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Ecological pressures demand that the public sector integrate sustainability into employee performance, but the underlying psychological mechanisms are still limited. This study examines the effect of Green OCB and Green Transformational Leadership (GTL) on Employee Performance through Green Work Engagement (GWE) as a mediator. A quantitative study on employees of the Environmental Agency used PLS-SEM analysis with SmartPLS and bootstrapping. The results showed that Green OCB and GTL had a significant positive effect on employee performance directly and on GWE. GWE also had a significant effect on performance, but the indirect effect through GWE was not significant, indicating that GWE did not mediate the relationship. It was concluded that voluntary pro-environmental behavior and green leadership improve employee performance directly without requiring GWE mediation, so direct implementation of sustainability values in the work practices of public organizations is important